2010
DOI: 10.1083/jcb.201004152
|View full text |Cite
|
Sign up to set email alerts
|

S-glutathionylation activates STIM1 and alters mitochondrial homeostasis

Abstract: Oxidant stress induces constitutive calcium entry by tacking glutathiones onto the Orai CRAC channel activator STIM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
189
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 205 publications
(204 citation statements)
references
References 61 publications
8
189
4
Order By: Relevance
“…We previously demonstrated that oxidants promote InsP 3 R-and STIM1-dependent Ca 2+ signaling and cell injury in LPS-challenged cells (14,15). These findings led us to speculate that blockade of the Ca 2+ permeation pathway could prevent LPSinduced lung inflammation and vascular injury.…”
Section: Ec-specific Stim1mentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that oxidants promote InsP 3 R-and STIM1-dependent Ca 2+ signaling and cell injury in LPS-challenged cells (14,15). These findings led us to speculate that blockade of the Ca 2+ permeation pathway could prevent LPSinduced lung inflammation and vascular injury.…”
Section: Ec-specific Stim1mentioning
confidence: 99%
“…Studies by us and others have demonstrated that ROS can modulate cytosolic Ca 2+ signals generated through inositol 1,4,5-tris phosphate receptor (InsP 3 R) Ca 2+ release channels in ECs (15). More recently, we revealed that ROS can induce STIM-mediated Ca 2+ entry via Orai channels by activating STIM proteins through S-glutathionylation of an evolutionarily conserved N-terminal cysteine residue in the STIM1 protein (14). Although ROS overproduction is an established event upon LPS challenge, it remains unclear whether ROS/STIM1 signaling participates in TLR4-dependent EC activation, vascular permeability, and lung injury.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations